Synthesis of Green Cerium Oxide Nanoparticles Using Plant Waste from Colocasia esculenta for Seed Germination of Mung Bean (Vigna radiata) - Nor Monica Ahmad; Nor’ Aishah Hasan (Journal of Nanotechnology)
Synthesis of cerium oxide (CeO2) nanoparticles (NPs) via biological approach has received a lot of interest to reduce the harmful effects of chemical synthesis. In the present study, Colocasia esculenta leaf extract facilitated the preparation of CeO2-NPs by using the sol-gel technique. The crystal structural of CeO2-NPs was proven by X-ray powder diffraction (XRD) investigation to be cubic with size of 2.94 nm according to Debye–Scherrer equation. As demonstrated in the transmission electron microscopy (TEM) image, CeO2-NPs have a spherical form with an average size of 2.04 nm which is almost consistent with a finding from XRD analysis. Energy dispersive X-ray (EDX) measurements exhibited high-intensity peaks attributed to Ce and oxygen and further proved the creation of CeO2-NPs. The Fourier transform infrared spectroscopy (FTIR) analysis revealed the presence of Ce-O stretching, indicating the formation of CeO2-NPs. Functional groups of O-H, C-O, and C=O peaks were found in a spectrum due to the phytochemical components that were responsible for reducing and stabilizing during the synthesis process of CeO2-NPs. The examined UV-visible spectra exhibited the absorbance peak at 213 nm. The synthesized NPs produced in this study were further investigated for mung bean seed germination, whereby the influence of grain germination and growth rate demonstrated the significant finding.